Canine Osteotomy Healing when Stabilized with Decreasingly Rigid Fixation Compared to Constantly Rigid Fixation - Egger, E.L.; Histand, M. B.; Norrdin, R. W.; Konde, L. J.; Schwarz, P. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
This study investigated the effect of destabilizing initially rigid external fixation of transverse canine tibial osteotomies, compared to contralateral osteotomies continuously stabilized, with rigid fixators. Destabilization, by conversion of a type III configuration fixator to a type I configuration, after one to four weeks resulted in increased periosteal callus formation but decreased mechanical strength and histologically a preponderance of fibrous and cartilaginous tissues in the osteotomy when studied after nine weeks. Destabilization at six weeks did not result in an increase in periosteal callus formation, nor greater bending strength. Histologically there was a combination of woven and lamellar bone, with the appearance of more active remodelling of primary bone healing. Destabilization at 12 weeks did not result in any effect, when studied after 15 weeks. These findings suggest that increasing weight-bearing loading of a fracture, at the proper time, may enhance the remodelling and hypertrophy of primary bone healing. However, inappropriate timing of destabilization may not have any or even a deleterious effect.Effects of reducing initially rigid fixation of canine tibial osteotomies, after various periods of time, were studied. Destabilization after one to four weeks caused increased periosteal callus formation but decreased mechanical strength. Destabilization after six weeks resulted in increased mechanical strength but no increase in periosteal callus, and destabilization after 12 weeks had no effect compared to osteotomies continuously stabilized with rigid fixation.
Keywords: Fracture fixation; fracture healing; fixation destabilization